PENGARUH KARAKTERISTIK DEWAN KOMISARIS DAN KOMITE AUDIT TERHADAP TINGKAT KONSERVATISME AKUNTANSI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2008-2010) - Wulandari, Dwinita; Zulaikha, Zulaikha (Diponegoro Journal of Accounting, 2012)
This study aims to examine the influence of board of commissioner’s and audit committee characteristics for accounting conservatism level. Accounting conservatism level is a dependent variable in this study that measured by accrual measurement. Independent variable in this study are independence commissioner proportion, commissioner board size, frequency of audit committee meeting, and competence of audit committee. This research also uses control variable that is firm size. The samples of  this  research  are  the  manufacturing  firms  listed  in Indonesian  Stock  Exchange  in  2008-2010. The samples are collected using purposive sampling   method and  resulted  33 firms become the samples. Data analyzed by classic assumption tests  and examination   hypothesis   by  multiple  linear  regression method. The result of this research show that frequency of audit committee meeting and competence of audit committee has significant effect to conservatism level measured by accrual.